Laparoscopic right hemicolectomy in situs inversus totalis with cecal carcinoma: a case report and literature review - Su, Bowen; Zhong, Yang; Chen, Jiahan; Tian, Hongpeng; Wu, Tianhao; Zhang, Guangjun (Frontiers in Oncology, 2025)
BackgroundOur patient exhibited situs inversus totalis (SIT)—a developmental quirk resulting in right–left transposition of all visceral organs, including the heart, liver, and spleen. While prior case reports have described colorectal carcinoma in individuals with SIT, to our knowledge, this case represents an exceptionally rare presentation of primary cecal carcinoma within this anatomical context. This case describes a patient undergoing laparoscopic right hemicolectomy for adenocarcinoma of the cecum.Case presentationA patient presented to our institution in May 2024. Subsequent diagnostic workup confirmed a diagnosis of cecal carcinoma. Given the absolute contraindication for bowel preparation secondary to complete bowel obstruction, along with radiologically confirmed cecal malignancy and elevated serum tumor markers, a multidisciplinary consensus was reached to proceed with laparoscopic right hemicolectomy after obtaining proper informed consent from the patient’s family. Pathology confirmed a T3N0M0 well-differentiated adenocarcinoma. Twelve-month consecutive postoperative follow-up data confirmed the absence of surgical complications such as anastomotic leakage or infection, as well as no clinical or radiographic evidence of disease recurrence.ConclusionAlthough the reversed anatomy in SIT patients presents inherent technical challenges for laparoscopic surgery, this minimally invasive approach can still achieve comparable safety and efficacy to conventional procedures when performed by experienced surgeons with adequate anatomical understanding.